Analysis of a Circular Water Tank Considering Lateral Load Using Analysis Tool a Review - Kusum; Pradeep Nirmal; Pratik Kathale (International Journal of Scientific Research in Civil Engineering, 2025)
Circular water tanks are widely used in water distribution systems due to their efficient design and cost-effectiveness for storing moderate water volumes. However, ensuring their structural integrity under water pressure and external loads is crucial. This research utilizes STAAD Pro, a popular structural analysis and design software, to model and analyze a circular water tank, evaluating its response to various loading conditions. The analysis process involves creating a three-dimensional model of the water tank within STAAD Pro. The model incorporates key geometric parameters such as tank diameter, wall thickness, roof and floor slab thicknesses, and support conditions. Material properties for concrete and steel reinforcement are defined based on relevant design codes. Following model generation, appropriate loading conditions are applied, including self-weight of the structure, hydrostatic pressure due to water content, and potential wind or seismic loads depending on the intended location.